2013
DOI: 10.1371/journal.pone.0081260
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends of the Abdominal Aortic Aneurysms Epidemic in General Population - A Meta-Analysis

Abstract: ObjectiveTo conduct a meta-analysis assessing the prevalence and trends of the abdominal aortic aneurysms (AAA) epidemic in general population.MethodStudies that reported prevalence rates of AAA from the general population were identified through MEDLINE, EMBASE, Web of Science, and reference lists for the period between 1988 and 2013. Studies were included if they reported prevalence rates of AAA in general population from the community. In stratified analyses possible sources of bias, including areas differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
152
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(170 citation statements)
references
References 76 publications
5
152
0
1
Order By: Relevance
“…The metaanalysis by Cornuz et al [16] of eight population-based risk factor studies of AAA showed that a history of PAD was a major risk factor or risk indicator for screening-detected AAA (OR, 2.48; 95% CI, 2.10 to 2.92). A meta-analysis by Li et al [17] of three epidemiological studies also showed that claudication was a risk factor for AAA (OR, 3.00; 95% CI, 1.74 to 5.19). However, although the association of PAD with AAA growth is still debated, PAD may be not [12] or even negatively [9,19] associated with AAA growth despite its positive association with AAA presence [16,17].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The metaanalysis by Cornuz et al [16] of eight population-based risk factor studies of AAA showed that a history of PAD was a major risk factor or risk indicator for screening-detected AAA (OR, 2.48; 95% CI, 2.10 to 2.92). A meta-analysis by Li et al [17] of three epidemiological studies also showed that claudication was a risk factor for AAA (OR, 3.00; 95% CI, 1.74 to 5.19). However, although the association of PAD with AAA growth is still debated, PAD may be not [12] or even negatively [9,19] associated with AAA growth despite its positive association with AAA presence [16,17].…”
Section: Discussionmentioning
confidence: 94%
“…A meta-analysis by Li et al [17] of three epidemiological studies also showed that claudication was a risk factor for AAA (OR, 3.00; 95% CI, 1.74 to 5.19). However, although the association of PAD with AAA growth is still debated, PAD may be not [12] or even negatively [9,19] associated with AAA growth despite its positive association with AAA presence [16,17]. Bhak et al [12] found no independent association between claudication and AAA expansion rates (adjusted MD, -0.1 mm/year; 95% CI, -0.6 to 0.3 mm/year; P = 0.52).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations